2019
DOI: 10.1080/14606925.2019.1595428
|View full text |Cite
|
Sign up to set email alerts
|

Ethics by Design. Exploring Experiences of Harmony and Dissonance in Ethical Practice.

Abstract: The positioning of design research as a response to complex challenges across disciplines, underpinned by participatory approaches highlights both a growing awareness of the discipline, and the recognition that design can offer a new perspective for exploration and innovation. However, critical to successful adoption of design research methodologies is an understanding of ethical practices that are inherent within the discipline. This paper presents the findings of two participatory design workshops entitled '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Findings from their research revealed that noticing, reflecting, and reacting were three dominant ways in which practitioners approach ethical issues within their organization. Tulloch et al [54] argued that design researchers must recognize their position within their organization's ethical ecology to be able to determine approaches that will support them to induce meaningful change. d'Aquin et al [15] advocated for the need to include data scientists in the discourse around ethics and developed an "Ethics by Design" research methodology for conducting research in the fields of AI and Data Science.…”
Section: Ethical Design Complexity and The Challenges Of Supporting E...mentioning
confidence: 99%
“…Findings from their research revealed that noticing, reflecting, and reacting were three dominant ways in which practitioners approach ethical issues within their organization. Tulloch et al [54] argued that design researchers must recognize their position within their organization's ethical ecology to be able to determine approaches that will support them to induce meaningful change. d'Aquin et al [15] advocated for the need to include data scientists in the discourse around ethics and developed an "Ethics by Design" research methodology for conducting research in the fields of AI and Data Science.…”
Section: Ethical Design Complexity and The Challenges Of Supporting E...mentioning
confidence: 99%